Panorama de expansão de geração de energia através de painéis fotovoltaicos - Bianco Neto, Arnaldo (Universidade Federal de São Carlos, 2021)
Starting with a brief explanation about the excitation of electrons in valence and conduction band when a pn junction of a silicon crystal semiconductor with impurities is enlightened, which its working state in reverse bias is similar to the one of a diode, the theory that allows the usage of solar modules to create tension and current was developed, as well as the maximum power point under work. Following in an technical and objective manner, a small sized installation project for households was designed under few simple premises and that were able to supply the average residential consumption for any of the country’s geographic areas so that it allows to determine where would happen the minor and major impacts of such installation of a decentralized generating power unit regardless of its proportions. Through official government ministry’s data, future value expectancy information was extracted, from both electrical bills and consumption. It let testing and project’s validation that it was capable of providing sufficient electrical power to the average residential consumption even though there is variability in the solar radiation on the territory. North and Northeast regions had the highest and lowest relative raises in the bills’ prices (before taxes) until the suggested mark at the year of 2028. With the targets for a full analysis completely defined, economic viability indicators for both were observed, such as internal return rate and discounted payback time for a minimum attractive rate of return based on the review of a wind project (Macedo, Albuquerque e Moralles, 2015). The North hit an internal rate of return of 12,83% with a discounted payback time of 9 years and 8 months for an amount of produced energy able to supply for over two average households in the region. However, in the Northeast, the internal rate of return was 7,01% and the time it took to pay the invested capital was 13 years and 1 month, nonetheless it was capable to supply around three houses with an average consumption that was found. Lastly, the environment is conducive to sustain the growth rate seen in the literature review by many reasons that aren’t all related to an strategical economical decision and this mood could be backed up by certain political choices highlighted in this and other researches on the Brazilian energy matrix.
Overview of power generation expansion through photovoltaic panels
Keywords: Geração de energia; Painéis fotovoltaicos; Energia solar; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA